(untitled) (International Journal of Engineering and Computer Science, 2015)
Determining the position of sensors is a very essential part for most WSN algorithms. When neighbor recognition fails, protocols performance and communications deteriorate. In networks affected by relay attacks the failure may be more precise. In this paper, we propose and discuss a technique that aims to circumscribe all the sensor nodes in the network using distance bounding which is a secure neighbor detection method by using secure localization. For this, we used trust based position identification for finding the position of the sensor nodes in the neighbor by applying trust based distance bounding protocol.